Pengaruh Media Sosial dan Game Online Terhadap Pelaksanaan Ibadah Siswa Kelas X Desain Komunikasi Visual SMKN 01 Bengkulu Selatan - Agung Wahyudin (UIN Fatmawati Sukarno Bengkulu, 2024)
The aim of this research is to analyze descriptions of the use of social media and online games among students at SMKN 01 Bengkulu Selatan, Manna District, South Bengkulu Regency, analyze descriptions of the implementation of student worship at the school, and determine the influence of the use of social media and online games on the implementation of worship. students at that school. This research uses a quantitative approach that is correlational, namely research that, apart from looking for relationships, is also used to predict between one variable and another variable. In this study the population was 115 students. Meanwhile, determining the sample size from a population of 28 samples used a technique developed by Suharsimi Arikunto, with an error rate of 25%. The research results show that 1). description of the use of Instagram social media among Class X Visual Communication Design students at SMKN 01 South Bengkulu, the percentage is 100%. Meanwhile, 28 respondents used mobile legend online games; Those who use it are 24 respondents with a percentage of 86%, and those who don't use it are 4 respondents with a percentage of 14%, 2). description of the implementation of fardhu prayers 5 times a day, students of class 6(21%) answered never and 3). The influence of the use of social media Instagram and the Mobile Legend online game on students' implementation of fardhu prayers is very significant, namely 72.0%. Meanwhile, 28% is influenced by other variables.